Investigation of Gamma Radiation Shielding in NiMnGa-Doped Multifunctional Smart Polymer Composites Using Geant4 and WinXCOM - Kaya, Mustafa; Kuzu, Serpil Yalcin; Niksarlıoğlu, Seçil; Pekdemir, Mustafa Ersin; Kök, Mediha (My University, 2024)
This study assesses the gamma radiation shielding efficiency of polymer composites doped with varying amounts of alloy, using software to demonstrate the potential application of innovative materials in radiation protection. Specifically, Poly Lactic Acid (PLA) and Poly Ethylene Glycol (PEG) composites doped with NiMnGa at concentrations of 2, 6, 10, and 15% were analyzed across an energy range of 0.0595 to 1.41 MeV using Geant4 and WinXCOM software. The radiation protection ability of the composites and the pure alloy were assessed by calculating key parameters, including the mass attenuation coefficient (?m), linear attenuation coefficient (?), half value layer (HVL), tenth value layer (TVL), and mean free path (MFP). The analyses indicated strong agreement between the results obtained from Geant4 and WinXCOM, demonstrating the performance of the software in investigating the radiation shielding characteristics of polymer-based materials. It was investigated that increasing the amount of NiMnGa in the composite structure significantly enhanced its radiation shielding capabilities. Notably, composites with 15% NiMnGa exhibited superior performance, comparable to traditional heavy metals, while maintaining the lightweight and flexible nature of polymer-based materials. The strong agreement between Geant4 and WinXCOM results further validates the computational approach. These findings highlight the potential of NiMnGa-doped polymer composites as eco-friendly, cost-effective alternatives to lead-based shields for medical and industrial applications, offering enhanced protection with reduced toxicity and environmental impact.
Keywords: Composites; gamma rays; polylactic acid (PLA); Alloy; polyethylene glycol (PEG)